2023
DOI: 10.1021/acsami.3c01735
|View full text |Cite
|
Sign up to set email alerts
|

Engineering UiO-68-Typed Homochiral Metal–Organic Frameworks for the Enantiomeric Separation of Fmoc-AAs and Mechanism Study

Abstract: Homochiral metal−organic frameworks (HMOFs) have been widely investigated in the application of enantiomeric separation. Nonetheless, it remains a significant challenge to explore the effect of multiple weak interactions between HMOF adsorbents and chiral adsorbates on enantiomeric separation performance still. In this work, robust chiral amine-alcohol-functionalized UiO-68-typed Zr-HMOFs 1−3 with the same hydrogen-bonding sites but slightly different π-binding sites were prepared for the enantioseparation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…1a, which create a unique asymmetric environment for the recognition and discrimination of the enantiomers. 46–49…”
Section: Resultsmentioning
confidence: 99%
“…1a, which create a unique asymmetric environment for the recognition and discrimination of the enantiomers. 46–49…”
Section: Resultsmentioning
confidence: 99%
“…This separates the D-ephedrine from the racemate (Figure 9). Wu et al [85] prepared three isochiral UiO-68 type Zr-HMOFs1-3 as adsorbents, which showed rapid adsorption and high adsorption capacity for amino acid derivatives (Fmoc-AAs), but their adsorption of enantiomers showed different enantioselectivity, and materials 1 and 2 showed preferential adsorption for Fmoc-L-Val. Material 3 showed preferential adsorption of Fmoc-L-Phe and Fmoc-D-Try.…”
Section: Adsorption Separationmentioning
confidence: 99%
“…Homochiral metal–organic frameworks (HMOFs), as an emerging class of chiral crystalline porous materials, have gained widespread attention for their intriguing applications in asymmetric catalysis, 1–3 enantioseparation, 4–8 chiral recognition 9–12 and other areas of asymmetry. Nevertheless, despite the appealing characteristics of HMOFs, such as their controlled synthesis, extraordinary porosity and highly accessible chiral functional sites, the limited chemical stability of most reported highly porous HMOFs has immensely hindered their industrial implementation.…”
Section: Introductionmentioning
confidence: 99%